Protocol and statistical analysis plan for the Antibiotic Choice On ReNal outcomes (ACORN) randomised clinical trial. Issue 3 (10th March 2023) - Qian, Edward Tang; Casey, Jonathan D; Wright, Adam; Wang, Li; Siemann, Justin; Dear, Mary Lynn; Stollings, Joanna; Lloyd, Bradley Daniel; Seitz, Kevin; Nelson, George; Wright, Patty; Siew, Edward D; et al.
Abstract : Introduction: Antibiotics are time-critical in the management of sepsis. When infectious organisms are unknown, patients are treated with empiric antibiotics to include coverage for gram-negative organisms, such as antipseudomonal cephalosporins and penicillins. However, in observational studies, some antipseudomonal cephalosporins (eg, cefepime) are associated with neurologic dysfunction while the most common antipseudomonal penicillin (piperacillin–tazobactam) is associated with acute kidney injury (AKI). No randomised control trials have compared these regimens. This manuscript describes the protocol and analysis plan for a trial designed to compare the effects of antipseudomonal cephalosporins and antipseudomonal penicillins among acutely ill patients receiving empiric antibiotics. Methods and analysis: The Antibiotic Choice On ReNal outcomes trial is a prospective, single-centre, non-blinded randomised trial being conducted at Vanderbilt University Medical Center. The trial will enrol 2500 acutely ill adults receiving gram-negative coverage for treatment of infection. Eligible patients are randomised 1:1 to receive cefepime or piperacillin–tazobactam on first order entry of a broad-spectrum antibiotic covering gram-negative organisms. The primary outcome is the highest stage of AKI and death occurring between enrolment and 14 days after enrolment. This will be compared between patients randomised to cefepime and randomised to piperacillin–tazobactam using an unadjusted proportional odds regression model. The secondary outcomes are major adverse kidney events through day 14 and number of days alive and free of delirium and coma in 14 days after enrolment. Enrolment began on 10 November 2021 and is expected to be completed in December 2022. Ethics and dissemination: The trial was approved by the Vanderbilt University Medical Center institutional review board (IRB#210591) with a waiver of informed consent. Results will be submitted to a peer-reviewed journal and presented at scientific conferences. Trial registration number: NCT05094154 .